Early Intervention for Children with Visual Impairment - Zusfindhana, Inna Hamida; Megaswarie,, Rosika Novia; Ariyanto,, Dedy; Prystiananta, Nostalgianti Citra (Department of Special Education, 2019)
Children with visual impairment tend to fail in understanding body images accurately, as a result of limited exploration, limited movement, and overprotective which will affect the delay in motor development. BS is a child with visual impairment who has obstacles in the process of orientation and mobility. So that it requires an early intervention program that is expected to be able to help BS to get to know their environment. Early intervention programs that will be applied to BS are orientation and mobility. This research uses a descriptive method with a qualitative approach. The research data was obtained through observation, interviews, and documentation. The results showed that before the early intervention BS got a score of 65, because BS had not yet understood the concept of early intervention. After early intervention the BS value shows an increase of 90.